Evaluating Students' Understanding of Kinetic Particle Theory Concepts Relating to the States of Matter, Changes of State and Diffusion: A Cross-National Study - Treagust, David; Chandrasegaran, Arulsingam; Crowley, Julianne; Yung, B.; Cheong, I.; Othman, J. (National Science Council, Taiwan (Springer), 2010)
This paper reports on the understanding of three key conceptual categories relating to the kinetic particle theory: (1) intermolecular spacing in solids, liquids and gases, (2) changes of state and intermolecular forces and (3) diffusion in liquids and gases, amongst 148 high school students from Brunei, Australia, Hong Kong and Singapore using 11 multiple-choice items that required students to provide explanations for their selection of particular responses to the items. Students’ responses to the items revealed limited understanding of the particle theory concepts, with nine alternative conceptions held by more than 10% of various samples of students. Also, 40.5–78.4%of all students indicated consistent understanding relating to the three conceptual categories based on their responses to the 11 items. However, when their explanations were taken into account, very few students displayed consistent understanding of the related concepts.